Respuesta :

Answer:

x = 1; y = 5

Step-by-step explanation:

-2x + 3y = 13 ;

y = 7x - 2

Since the second equation is already solved for y, substitute y of the first equation with 7x - 2.

-2x + 3y = 13

-2x + 3(7x - 2) = 13

-2x + 21x - 6 = 13

19x - 6 = 13

19x = 19

x = 1

Now substitute x of the second equation with 1 and solve for y.

y = 7x - 2

y = 7(1) - 2

y = 7 - 2

y = 5

Solution: x = 1; y = 5

Answer:

shoot this is wrong dont look

Step-by-step explanation:

If I know this...

You would have to plug in y in equation two for y in equation one. So it would become:

-2x+3(7x-2)=13

And simplifying that further it would be:

-2x+21x-6=13

Combining like terms would looks like this:

19x=7

And solving for x would looks like this:

x=7/19